The Effects Of Interpersonal Communication, Work Ethic And Leadership Style Towards Junior High School Teacher Performance In Tomohon City - Tuerah, P R (Universitas Negeri Manado, 2019)
This study aims to determine the effect of interpersonal communication, work ethics and leadership style on teacherâ€™s performance in the city of Tomohon. The sample of this study used 195 respondents. Data were collected from four variables which were examined and analyzed using correlation and regression techniques. The results of this study indicate that (1) Interpersonal communication has a positive influence on performance, (2) Work ethic has a positive influence on teacher performance, (3) Performance has a positive influence on teacher job satisfaction and (4) Interpersonal communication, work ethics and leadership styles together have a positive influence together on teacher performance. These variables show that there is a positive relationship to teacher performance and thus all hypotheses in this study were accepted.Â Keywords: Interpersonal communication; work ethics; leadership; teacherâ€™s performance.